2012
DOI: 10.3349/ymj.2012.53.5.915
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Experience with the Bentall Procedure: 28 Years

Abstract: PurposeWe retrospectively analyzed 28 years of experience with the Bentall procedure in patients with aortic valve, aortic root, and ascending aortic disease.Materials and MethodsBetween March 1982 and December 2010, a total of 218 patients underwent the Bentall procedure using a composite valved conduit. The "inclusion technique" was used in 30 patients (13.8%), the "open-button technique" in 181 patients (83.0%), and the Cabrol technique in 7 patients (3.2%).ResultsThe early mortality rate was 5.5% (12/218).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
2
34
0
4
Order By: Relevance
“…Joo and colleagues 23 reported a hospital mortality of 5.5% in 12 patients, with the mean cause low cardiac output syndrome in 3 (25%), arrhythmia in 3 (25%), pneumonia in 2 (17%), sepsis in 2 (17%), and others.…”
Section: Hospital Mortalitymentioning
confidence: 96%
“…Joo and colleagues 23 reported a hospital mortality of 5.5% in 12 patients, with the mean cause low cardiac output syndrome in 3 (25%), arrhythmia in 3 (25%), pneumonia in 2 (17%), sepsis in 2 (17%), and others.…”
Section: Hospital Mortalitymentioning
confidence: 96%
“…In a recently reported 28 years experience (from 1982) of the Bentall procedure, the operative mortality was 5.5%, and risk of late reoperation and endocarditis were 3.2% and 1.4% respectively 6). Moreover, Lim et al6) reported that, in patients with aortic root dilatation with advanced aortic regurgitation, operative mortality was 2.4% in the Bentall procedure group and 0% in the valve-sparing operation group 7). Compared with those data, in patients with CARVAR surgery, mortality seems quite higher than recently reported results and the risk of endocarditis and re-operation are much higher than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that long‐term survival is improved with the open‐button technique. However, despite these technical modifications of the Bentall procedure, complications have not been completely eliminated . The interval between the initial procedure and the development of pseudo‐aneurysm can be long, up to 17 years .…”
Section: Discussionmentioning
confidence: 99%